Memory, Trauma and Forgetting in Northern Irish Drama - Anthony Roche (Review of Irish Studies in Europe)
The ethical exhortation ‘not to forget’ runs the risk of ‘a memory that would never forget anything’. At the other extreme is the no less dangerous risk of total amnesia, an erasure of the past that immediately suggests Freud and the return of the repressed. The complex balance to be found between memory and forgetting is particularly fraught in Northern Ireland and the politics of how the past is to be negotiated in the current post peace process climate. I propose to look at this subject in relation to the trauma engendered by decades of violence in two Northern Irish plays: Quietly (2012) by Owen McCafferty, set in the post peace process climate of 2009 but harking back to a violent incident in the same location thirty-five years earlier; and Frank McGuinness’s Carthaginians (1988), a canonical play about one of the central events in ‘the Troubles’, Bloody Sunday of 30 January 1972, but set more than a decade later.